Estudo fitossociológico de floresta estacional semidecidual e de cerrado no município de Patrocínio Paulista, SP - Teixeira, Maria Inês Junqueira Garcia [UNESP] (2003)
The need to know more about the vegetation of the northwestern region of São Paulo state becomes more and more urgent, due to the accelerated destruction of this vegetation. The objective of this work was to conduct a f10ristic inventory and analise phytosociological parameters in an area of semideciduous seasonal forest (A and B) and an area of cerrado stricto sensu (C) of Latosolic Structured Red Earth (Red Nitosol Eutroferic) soil, Red- Ye 11 ow Podzolic and Quartzpsamment soil, respectively, in Santa Cecília's farm, municipality Patrocínio Paulista, São Paulo State, Brazil (20046' 12 Se 47014' 24 W), 800/ 850 m of altitude. Ninety plots of 10m x 10m were established and there were registered 1255 arboreal individuais GBH ~ 15 cm, in A area, belonging to 58 species and 29 families, in B area, 66 species and 32 families and C area, 53 species and 30 families. The families that showed the highest number of species were in A: Rubiaceae (7), Myrtaceae (6), Meliaceae (5), Lauraceae and Fabaceae (4), in B: Meliaceae (8), Euphorbiaceae (6), Mimosaceae, Myrtaceae and Sapindaceae (4) and C: Fabaceae (7), Myrtaceae (5) and Vochysiaceae (4). The species with the highest importance value (IV) were in A: Micrandra e/ata (74,11), Aspidosperma ramiflorum (14.58) and Aspidosperma po/yneuron (14,04), in B: Urera baccffera (34,51), Croton piptoca/yx (29,85) and Ficus gomeI/eira (24,19) and in C: Qua/ea grandff/ora (62,38), Da/bergia misc%bium (22,24), Styrax camporum (21,86). Shannon's index (H') for A, B and C áreas were respectively 3,39, 3,40 e 3,05 and Similarity Jaccard's index (ISj) was 36,95% compared to A and B area.